Improvement of Quality of Life Based on Study of the Drainage System in the City of Belém/PA - Rodrigues, Leonardo Teles (2023)
Water is a factor present in human life at all times of its existence. The correct management of it, whether for the supply and enjoyment of social needs, or the control of rainwater and the like are challenges present in virtually all major population centers in the world. In this way, the present research aimed to study the Canal da Avenida Doutor Moraes, in Belém/PA, inserted in the Estrada Nova Hydrographic Basin, to evaluate its performance conditions, the authorities' care for this system, the users' responsibility, and the physical state and conservation of its micro and macro drainage components. The canal cuts through several avenues in the neighborhood of Batista Campos, being very close to the neighborhoods of Cremação and Jurunas. The components of the Canal are well preserved due to a certain awareness of local residents and a well-defined agenda of the competent authorities that carry out periodic cleaning in the place, in addition to plans for dredging the channel, which in a certain section suffers from silting. The problems only revolve around occasional situations of disrespect on the part of users who irresponsibly dump residential solid waste, in addition to making clandestine connections without due care for the channel's reinforced concrete structure. Finally, it was observed that the systems can only be preserved with the union and joint work of the public power with the population, where each one performs its role before the responsibilities for the rights and duties can maintain the necessary balance for the well-being of the population as a whole.